Detection of hemoglobin concentration in human blood samples using a zinc oxide nanowire and graphene layer heterostructure based refractive index biosensor - Ansari, Gufranullah; Pal, Amrindra; Srivastava, Alok K.; Verma, Gaurav (Optics and laser technology, 2023)
•Five layered surface plasmon resonance based optical biosensors designed for haemoglobin measurement in human blood samples.•Silver metal, zinc oxide nanowires (ZnO NWs), graphene nanolayers, and a BK7 prism have been used to design the suggested SPR sensor.•Vapor-liquid–solid (VLS) fabrication was used to create the ZnO NWs.•The suggested sensor can be used for detection and analysis of the biomolecules and may provide real time monitoring and label free sensing. The present study proposes five layered surface plasmon resonance based optical biosensors designed for hemoglobin measurement in human blood samples. Silver metal, zinc oxide nanowires (ZnO NWs), graphene nanolayers, and a BK7 prism have been used to design the suggested SPR sensor. The analysis was performed after modeling it using ZnO nanowire and graphene layers over the conventional sensor design. This optimized nanostructure uses the difference in refractive index to identify hemoglobin content in human blood. Vapor-liquid–solid (VLS) fabrication was used to create the ZnO NWs. The maximum sensitivity of the suggested configuration is 207°/RIU, and other parameters FWHM of 5.937°, the signal-to-noise ratio of 0.168°-1, and a quality factor of 34.78 RIU−1 have been obtained. The suggested sensor may be used to detect and analyze biomolecules.